Coating based on Montmorillonite, essential oils, and amaranth to preserve mango - Evelyn Erika Pillco Ramos; Maria Cecilia Pacco-Huamani; Sandriane Pizato; Rosalinda Arévalo Pinedo; William Renzo Cortez-Vega; Grethel Teresa Choque Delgado (Polímeros)
Abstract This study aimed to evaluate the coating based on Amaranthus flour (AF), montmorillonite, and three essential oils (clove, muña, and matico) to extend the shelf life of minimally processed mango. The mango cubes were divided into four different treatments. T1- control (uncoated mango), T2 (0.3% w/v of clove), T3 (0.3% w/v of muña), and T4 (0.3% w/v of matico). All treatments had 0.6% w/v Amaranth flour and 0.02% w/v montmorillonite (MMT) and were subjected to 5°C for 12 days. Water activity (Aw), pH, Total soluble solids, acidity, weight loss, color, texture, and antimicrobial activity were evaluated for each treatment. Matico treatment maintained pH and had the lowest count of yeast and mold forming units on mango (3.47 log UFC g-1). On the last day of storage, all coating treatments showed less weight loss and favorable results than the control. The matico treatment showed higher efficiency for mango preservation.